Protective Effect of Mesenchymal Stem Cells Derived Secretome in an in Vitro Pro-Inflammatory Model of Intervertebral Discogenic Pain (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: discogenic pain; mesenchymal stem cells; secretome; immunomodulation